OC-047 Adenoma Surveillance In The National Nhs Bowel Cancer Screening Programme – Is The High/intermediate Risk Stratification Appropriate?. (9th June 2014) - Majumdar, D; Hungin, AP; Wilson, DW; Bramble, M; Rutter, MD
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) guidelines advocate surveillance of high and intermediate risk subjects with adenomas, due to the risk of developing future advanced neoplastic lesions. This study aims to evaluate and compare the yield of colorectal neoplasia during first surveillance in NHS BCSP among these two cohorts. Methods: Data on each patient entering the NHS BCSP are contemporaneously recorded on the national BCSP database (BCSS). BCSS was interrogated to identify all high-risk (HR) and intermediate-risk (IR) subjects at screening who completed their first surveillance episodes during the period of June 2006 to July 2012. Participants with histology data available at surveillance were included. The data were then analysed to assess the detection of colorectal cancer (CRC), advanced adenoma (size ≥10 mm/ > 25% villous histology/ high grade dysplasia) and non-advanced adenoma in the two groups. Chi-square tests were performed to determine significance of difference in proportions among them. Results: Table showing subjects with different pathologies at first surveillance: During the study period 5579 HR and 4723 IR subjects completed their first surveillance procedures, of which 5118 HR and 4569 IR subjects had their histology results available, and were included for final analysis. 39 (0.76%) HR and 20 (0.47%) IR subjects were diagnosed with colorectal cancer (CRC). Detection of CRC and colorectal adenomas during the first surveillance were significantly higher in HR group (table). Conclusion: Only a small number of subjects had CRC during their first surveillance, indicating that the current surveillance intervals for HR and IR groups are safe. The higher yield of all colorectal neoplasia (CRC, AA and NAA) during the first surveillance in HR subjects illustrates that the current risk stratification is valid and justified. The finding of significant and higher proportion of IR subjects with non-neoplastic findings during first surveillance suggests that, they have less potential to develop colorectal neoplasia and further study needed to evaluate whether their surveillance interval can be safely prolonged. Reference: 1 Guidelines for colorectal cancer screening and surveillance in moderate and high risk groups (update from 2002). Gut 2010;59:666–690 Disclosure of Interest: None Declared.